Climate values as predictor of climate change perception in the Kingdom of Saudi Arabia - Arnout, Boshra A. (Frontiers in Psychology, 2022)
Background: Understanding public perceptions of climate change and how individuals perceive it is critical to developing effective communication strategies, policies, and socially robust technologies to relieve the risks of climate change. Despite the growing literature on climate change, until now, the researchers in the Arab countries have not been interested in studying citizens' perceptions of climate change or seeking to identify the factors that predict it. This study aimed to identify and understand the nature and dynamics of public perceptions of climate change among Arab citizens and detect the level of climate change perception CCP and climate values CV. Also, to detect the predictability of CCP from CV. As well as to reveal the differences in CCP and CV. Method: A random sample consisted of 465 participants (236 male and 229 female), residents of the Kingdom of Saudi Arabia; their ages ranged from 30 years and over. The Climate Change Perception Questionnaire (PCCQ) and Climate Values Questionnaire (CVQ) were applied online. Results: The results found average levels of climate change perception (CCP) and climate values (CV) among the study sample. The results also revealed significant statistical differences in the CCP and CV due to gender in favor of females. As well as, there were significant statistical differences in the CCP due to the career field in favor of agriculture, engineering, and construction workers. Also, there were statistical differences in the emotional subscale of climate perception and climate values due to age groups in favor of individuals whose ages ranged from 30 to 45 years. The results also found that the climate values were a statistically significant predictor (1.2 % of total variance) of climate perception.